Shadowing Technique; Teaching Listening Skill to ESOL Learners in University - Ginting, Siti Aisyah (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2019)
The purpose of this paper is to report the effect of Shadowing Technique on students’ listening skills achievement. Therefore, the experimental research was applied and the technique on collecting the data was administrating pre- and post- tests to the experiment and control groups, which consisted of 40 students in each group. Then, t-test was employed on analyzing the data. As a result, there was a significant difference between the mean of experimental and control groups (F = 8.92, p=. 003 < .05). Therefore, there was a significant effect of applying shadowing technique on students’ listening skill achievements and the experimental group outperformed the control group. To sum up, the alternative hypothesis was accepted and the null hypothesis was rejected.